Floral, fruiting, and staminal morphology of Vandellia L. (Lamiales, Linderniaceae) from India, with three new combinations - Pal, Aaratrik; Chowdhury, Monoranjan (Phytotaxa, 2025)
Vandellia L. (Linderniaceae) shows diversity in calyx, staminal and fruiting morphology. Recent studies also reported polyphyletic nature of Vandellia. Morphological delimitation of true Vandellia from Torenia and the recently established Yamazakia is discussed in this paper with illustrations. Three new combinations, including one Torenia and two Yamazakia, based on our morphological studies of Indian Vandellia, are proposed, together with photographs and key to the related taxa.